Corporate image and destination image: the moderating effect of the motivations on the destination image of Spain in South Korea - Pérez-Tapia, Gema; Mercade-Mele, Pere; Almeida-García, Fernando (Rouledge. Taylor and Francis Group, 2019)
The research objective is to analyse the destination image and corporate image of Spain among the Korean university population. We study the moderating effect of the motivation between two potential groups of tourists, escapers (tourists who travel for relaxation) and seekers (tourists who travel for seeking culture). Information was collected in South Korea via a questionnaire and the data were analysed using structural equation and multi-group analysis. For both groups, the results show that the corporate image has influence on the cognitive component of the destination image, motivation impacts on the cognitive and affective dimensions, and the cognitive component effects the affective component.
Keywords: Imagen corporativa; Corporate image; Destination image; Motivation; South Korea; Spain; Structural equation model